Global summary of baseline household survey results - Kristjanson, Patricia M.; Garlick, Cathy; Förch, Wiebke; Thornton, Philip K.; Cramer, Laura K.; Ndungu, Anthony (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This report summarises the results of a baseline household-level survey, designed by the CCAFS team and implemented in late 2010/early 2011 in 3 regions: East Africa, West Africa and South Asia. This survey was designed with the intent of developing simple, comparable cross-site household level indicators, for which changes can be evaluated over time, of food security, households assets, agricultural production diversity, agricultural sales diversity, changes being made in farming practices for adaptation, innovation, and/or to help reduce emissions or store greenhouse gases (mitigation), and gender indicators (e.g. men’s versus women’s reception of weather-related information). A standardised survey, guidelines and training materials were implemented across 12 countries in West Africa (Senegal, Mali, Burkina Faso, Niger, and Ghana), East Africa (Kenya, Uganda, Ethiopia, and Tanzania), and South Asia (India, Nepal and Bangladesh). Thus we have a total of 15 core sites covering 108 villages and 2095 households. This summary report gives an overview of the farming practices, and asset, livelihoods and food security status of rural households in these sites. It describes what changes farmers have been making in recent years with respect to crop management, livestock practices, use of inputs and other agricultural practices. We explore what kinds of weather/climate and associated information these households are receiving, how and by whom. This information provides important baseline information, as these households will be revisited in 5-10 years’ time in order to evaluate the changes in these indicators. This will give us important information as to if, how, and which households are adapting to a changing climate while improving their food security status.